Strategi Manajemen Sumber Daya Manusia Untuk Meningkatkan Kinerja Keuangan Perusahaan Dalam Bersaing Di Perekonomian Global - Ferra Eka Ramadhani,; Koslani, (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2023)
Global competition is indicated by the number of competitors operating in the world market, which causes every company to be able to manage its human resources to develop effectiveness in order to improve the finances of each company in competing in today's global era. This study aims to determine a good human resource management strategy to improve the quality of each company in competing in this global economy. The method used in this research is descriptive qualitative by observing the phenomena that occur at this time. The results of the study indicate that in order to improve the company's finances in competing in this global economy, the human resource strategy made must be in line with the goals of each company.